2005
DOI: 10.1063/1.2005399
|View full text |Cite
|
Sign up to set email alerts
|

Effective hole injection of organic light-emitting diodes by introducing buckminsterfullerene on the indium tin oxide anode

Abstract: We demonstrate that dramatically improved hole injection can be achieved by inserting a very thin C60 film between the indium tin oxide (ITO) electrode and N,N′-diphenyl-N,N′-bis(1,1′-biphenyl)-4,4′-diamine (NPB) layer. This result is ascribed to the formation of an interfacial dipole layer of buckminsterfullerene (C60) on the ITO electrode. The dipole layer induces the surface potential shift that contributes to improve the charge injection efficiency. The chemical shift was downward to help lower the hole in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…9 Hayashi et al reported that the vacuum level of metals such as Au, Cu, and Ag was affected by deposition of C60 and it induced interfacial dipole formation due to strong interaction between metals and C60. There has been another study about the interaction between oxide and C60, 5 but the study could not give information about the relationship between ITO surface properties and hole injection in C60 modified devices. Therefore, hole injection in C60 modified devices was correlated with ITO surface treatment and detailed mechanism of hole injection was elucidated in this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Hayashi et al reported that the vacuum level of metals such as Au, Cu, and Ag was affected by deposition of C60 and it induced interfacial dipole formation due to strong interaction between metals and C60. There has been another study about the interaction between oxide and C60, 5 but the study could not give information about the relationship between ITO surface properties and hole injection in C60 modified devices. Therefore, hole injection in C60 modified devices was correlated with ITO surface treatment and detailed mechanism of hole injection was elucidated in this work.…”
mentioning
confidence: 99%
“…4 Hong et al used C60 as a buffer layer on indium tin oxide ͑ITO͒ and the interfacial energy barrier between ITO and N, N'-di͑1-naphthyl͒-N, N'-diphenylbenzidine ͑NPB͒ was reduced by 0.5 eV by surface dipole formation. 5 Our group applied C60 as a buffer layer on Al electrode and observed 0.9 eV decrease of interfacial energy barrier. 6 Current density was increased by C60 buffer layer on Al and current efficiency was also improved by efficient hole injection from Al to light-emitting layer.…”
mentioning
confidence: 99%
“…In order to estimate the carrier confinement percentage in each EMLs with different CCL in double QW structure, the current density values are compared with the hole barriers obtained between HOMO levels of each CCL and Ir(piq) 3 . According to the thermionic emission barrier model (Hong et al, 2005), ln(J) has a good linear relationship with the potential barrier (Φ). Figure 4(b) shows a good agreement between ∆ln(J) and ∆Φ at 5V, indicating that the hole barrier is the main factor to determine the current flow in our devices.…”
Section: Resultsmentioning
confidence: 99%
“…With a thin layer deposited on Al such as WO 3 [5] or V 2 O 5 [6], the work function of Al is enhanced. Recent studies reveal that the work function of Al [7][8][9][10][11] or indium tin oxide (ITO) [12] is enhanced by coating a thin layer of fullerene (C 60 ). The enhancement could be ascribed to the electron transfer from Al or ITO to C 60 [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reveal that the work function of Al [7][8][9][10][11] or indium tin oxide (ITO) [12] is enhanced by coating a thin layer of fullerene (C 60 ). The enhancement could be ascribed to the electron transfer from Al or ITO to C 60 [9,12,13]. The effect of deposition of Al onto C 60 is different from that of C 60 onto Al, in which Al is less diffusive [8].…”
Section: Introductionmentioning
confidence: 99%